Determinants of initial public offerings (IPO) return in Malaysia / Mohd Nazirul Najmi Mohd Othman - Mohd Othman, Mohd Nazirul Najmi (2017)
The study is conducted to determine the relationship between Initial Public Offerings (IPO) return at the first trading day and its determinants. The observation is based on 41 newly-listed IPOs in Main Market Bursa Malaysia in between the year 2012 until 2014 and the data were gained from Bloomberg, Bursa Malaysia and Yahoo Finance. In order to study the relationship between initial return and its determinants, the researcher will gain the initial return data, which is the difference of issuance and the price of first day trading and run the data together with the independent variables such as size of issuance, age of the firm, offer price, listing delays and underwriter's reputation. Several tests will be conducted including the multi regression analysis. Lastly, all the independent variables had found insignificant with initial return except the offer price.